2022
DOI: 10.1039/d1em00545f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dissolved organic matter characteristics on the photosensitized degradation of pharmaceuticals in wastewater treatment wetlands

Abstract: Wastewater treatment wetlands are aquatic systems where diverse dissolved organic matter (DOM) compositions physically interact. Complex photochemical behaviors ensue, leading to uncertainties in the prediction of indirect photodegradation rates for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 135 publications
0
8
0
Order By: Relevance
“…16,25−30 In contrast, Φ • OH has the same trends as other PPRI or E 2 ;E 3 in some studies 24,31,32 but opposite trends in other studies. 17 the same pools of highly aliphatic DOM at the molecular level in several small sets of samples, 14,26,36 and we previously demonstrated that separate pools of DOM are strongly related to f TMP and Φ 1 Od 2 in comparison with Φ • OH . 14 However, these molecular level trends have not yet been tested in diverse waters.…”
Section: •−mentioning
confidence: 55%
See 3 more Smart Citations
“…16,25−30 In contrast, Φ • OH has the same trends as other PPRI or E 2 ;E 3 in some studies 24,31,32 but opposite trends in other studies. 17 the same pools of highly aliphatic DOM at the molecular level in several small sets of samples, 14,26,36 and we previously demonstrated that separate pools of DOM are strongly related to f TMP and Φ 1 Od 2 in comparison with Φ • OH . 14 However, these molecular level trends have not yet been tested in diverse waters.…”
Section: •−mentioning
confidence: 55%
“…The predominant quencher of 3 DOM is O 2 , which forms singlet oxygen ( 1 O 2 ) via energy transfer from 3 DOM. Both 3 DOM and 1 O 2 can react to transform some organic contaminants. ,, Autochthonous DOM or DOM originating from wastewater has been shown to be more photoreactive in terms of producing these PPRI. ,, Other PPRI, including hydrogen peroxide (H 2 O 2 ), superoxide, (O 2 •– ), and hydroxyl radical ( • OH), form through electron-transfer reactions, but exact pathways are less well understood. , The two predominant mechanisms discussed in the literature include reduction of O 2 or H-atom abstraction from water . Precursors for these PPRI may include 1 DOM, 3 DOM, charge-transfer species, or other photochemically excited complexes associated with DOM. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these chemical methods exhibit drawbacks such as long test period, high costs, and significant consumption of chemical reagents, making them difficult to meet the needs of real-time online monitoring. Optical methods provide advantages such as rapid detection, simple operation, and non-destructive sample analysis [7]. In recent years, with the advancement of new technologies such as optical and spectroscopic techniques, notably the emergence of three-dimensional fluorescence spectroscopy and UV-Vis absorption spectroscopy, rapid real-time monitoring of wastewater treatment plants has been rendered feasible [8][9].…”
Section: Introductionmentioning
confidence: 99%